Diskurzivne prvine v izbranih Trubarjevih predgovorih in pismih - Bošnjak, Blanka (Slavia Centralis, 2020)
Discursive Elements in Selected Trubar’s Prologues and Correspondence. The thesis of this paper is that, by means of analyzing Trubar’s selected prologues and correspondence, the following regularity is evident from the viewoint of discourse theory: in Trubar’s time discourse diversity tended to have some common starting points.